Computing Epistasis of Template Functions Through Walsh Transforms - Iglesias, María Teresa; Vidal, Concepción; Verschoren, Alain (Computing and Informatics, 2012)
Template functions have been introduced as a class of test functions, allowing to study the convergence behaviour of genetic algorithms. In this note, we show how to use Walsh transforms to calculate the normalized epistasis of these functions.